ASSESSING SEDIMENT REGIME ALTERATION OF THE LOWER DRAVA RIVER (Advances in Civil and Architectural Engineering, 2021)
Alterations to the sediment regime of the lower Drava River were assessed using the rescaled adjusted partial sums (RAPS) method and possible causes of these changes are discussed in this paper. The sudden alteration to sediment regime and the sharp decreases of suspended sediment concentration (SSC) at the two gauging stations in the lower Drava River began in the 1980s. Suspended sediment load decreased about 65% between 1967–1981 (0.922×106 t/year) and 2003–2017 (0.323×106 t/year) for the Botovo station. For the Donji Miholjac station, suspended sediment load decreased about 81% between 1971–1981 (1.383×106 t/year) and 2007–2017 (0.263×106 t/year). The construction and operation of reservoirs were the main reasons for these sharp alterations. SSC and flow discharge (Q) relationships were assessed by proposing a new form of a sediment rating curve (SRC). Compared with the traditional SRC approach, the new form of the SRC can better capture seasonal dynamics of SSC at daily and monthly time-scales.